Excess natural-cause deaths in California by cause and setting: March 2020 through February 2021. Issue 3 (8th June 2022) - Chen, Yea-Hung; Stokes, Andrew C; Aschmann, Hélène E; Chen, Ruijia; DeVost, Shelley; Kiang, Mathew V; Koliwad, Suneil; Riley, Alicia R; Glymour, M Maria; Bibbins-Domingo, Kirsten
Abstract: Excess mortality has exceeded reported deaths from Covid-19 during the pandemic. This gap may be attributable to deaths that occurred among individuals with undiagnosed Covid-19 infections or indirect consequences of the pandemic response such as interruptions in medical care; distinguishing these possibilities has implications for public health responses. In the present study, we examined patterns of excess mortality over time and by setting (in-hospital or out-of-hospital) and cause of death using death certificate data from California. The estimated number of excess natural-cause deaths from 2020 March 1 to 2021 February 28 (69, 182) exceeded the number of Covid-19 diagnosed deaths (53, 667) by 29%. Nearly half, 47.4% (32, 775), of excess natural-cause deaths occurred out of the hospital, where only 28.6% (9, 366) of excess mortality was attributed to Covid-19. Over time, increases or decreases in excess natural non-Covid-19 mortality closely mirrored increases or decreases in Covid-19 mortality. The time series were positively correlated in out-of-hospital settings, particularly at time lags when excess natural-cause deaths preceded reported Covid-19 deaths; for example, when comparing Covid-19 deaths to excess natural-cause deaths in the week prior, the correlation was 0.73. The strong temporal association of reported Covid-19 deaths with excess out-of-hospital deaths from other reported natural-cause causes suggests Covid-19 deaths were undercounted during the first year of the pandemic.